The effectiveness of basketball players offense, following an outside game, through video analysis - Tsamourtzis, E.; Mavridis, G.; Karipidis, A.; Rokka, S.; Sfiggos, N.; Athanailidis, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
An offensive strategy can include movements like shots with screen, without screen or shots near of far from the basket (Wissel, 2006). The outside game is part of the control offense and is based on shots performed from medium or far distances. The effectiveness -or not- of a shot depends on the amount of pressing applied on the defense, as well as on the personal characteristics of the player shooting (Smith & Spear, 1981). Many coaches prefer developing strategies far from the basket, so that all players can shoot (Gillen, 1993). The aim of this study was to analyze the outside game in European Championships. Methods The sample consisted of 80-videotaped Basketball games from the 2003, 2005 and 2007 Mail European Championships. The phases recorded were the outside game and the offenses with and without screen, as well as the effectiveness of the above offenses. To define effectiveness, the authors considered the successful or missed two-point and three-point shots, the won offenses and the turnovers. The following equipment was used: A video set to record the games shown on various channels; a video card for the digitalisation of the games; A computer (P/C); the "Sportscout" programme for the analysis of the digital video. For the statistical analysis of the data, the method used was the analysis of frequencies and the non-parametric test x2. The p< .05 was defined as level of significance. Results The outside game took up 65% of the executed offenses. 4 out of 10 of the offenses far from the basket were realized after a screen, while 6 out of 10 without a screen. The teams performed a higher score of two-point and three-point shots, after a screen. The dominant offense with screen was the pick and roll, while the most frequent offense without screen was the 1 on 1. Discussion The dominant offensive tactic without screen was the offense 1 on 1, which is in accordance with Tavares et al., 2003. As for the offenses without screen, the dominant element of control offense was the pick and roll (Ociepka, 2004; Filipovski, 2005). Both the distribution of the offensive strategy and the effectiveness of the players are similar to those of previous researches (Tavares et al., 2003). The development of an offensive strategy must satisfy players, coaches and fans, but it must also be successful (Wissel, 2006).